2006
DOI: 10.2105/ajph.2004.061507
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Industry Influence on Science and Scientists in Germany

Abstract: Using tobacco industry documents, we examined how and why the tobacco industry sought to influence science and scientists in Germany as a possible factor in explaining the German opposition to stricter tobacco regulation. Smoking and health research programs were organized both separately by individual tobacco companies and jointly through their German trade organization. An extensive network of scientists and scientific institutions with tobacco industry links was developed. Science was distorted in 5 ways: s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 33 publications
0
50
0
10
Order By: Relevance
“…Interviewees reported that the organisation was of the opinion that tobacco industry representatives had to be "heard as an affected party" (public health advocate), suggesting that the bridging organisation was far more accepting of consultations with tobacco industry representatives than more central members of the Supporters' Alliance, who argued that tobacco industry representatives should not be "asked", "consulted", "involved" or "have an input" in the development of smoke-free policy. A possible explanation for all bridging organisations being based in Germany might be that their positions in the network mirror the higher acceptance of the tobacco industry in German society and politics (Grüning & Gilmore, 2007;Grüning, Gilmore, & McKee, 2006).…”
Section: Interviewees Reported That the Opposing Views Of The Two Allmentioning
confidence: 99%
“…Interviewees reported that the organisation was of the opinion that tobacco industry representatives had to be "heard as an affected party" (public health advocate), suggesting that the bridging organisation was far more accepting of consultations with tobacco industry representatives than more central members of the Supporters' Alliance, who argued that tobacco industry representatives should not be "asked", "consulted", "involved" or "have an input" in the development of smoke-free policy. A possible explanation for all bridging organisations being based in Germany might be that their positions in the network mirror the higher acceptance of the tobacco industry in German society and politics (Grüning & Gilmore, 2007;Grüning, Gilmore, & McKee, 2006).…”
Section: Interviewees Reported That the Opposing Views Of The Two Allmentioning
confidence: 99%
“…Our study shows that the concept of stress is a further area of public health research that has been subject to extensive tobacco industry influence. Using the categories of industry influence identified by Gruning et al, 101 Selye's expert evidence diluted existing evidence of the adverse effects of smoking and distracted attention from its harms. In failing to declare his receipt of tobacco funding when expressing his views against tobacco control, documents suggest he concealed a lack of scientific independence; and by involving tobacco industry lawyers, Selye allowed the industry to manipulate the scientific process.…”
Section: Discussionmentioning
confidence: 99%
“…The industry has used quasi-scientific organisations and individuals to promote controversy and uncertainty, such as denying for as long as possible the health effects associated with passive smoking [10]. We must view with extreme scepticism funding of scientific research by the tobacco industry.…”
Section: Ending the Manipulationmentioning
confidence: 99%